2022
DOI: 10.1002/chem.202200809
|View full text |Cite
|
Sign up to set email alerts
|

On‐Surface Synthesis of Unsaturated Hydrocarbon Chains through C−S Activation

Abstract: We use an on-surface synthesis approach to drive the homocoupling reaction of a simple dithiophenyl-functionalized precursor on Cu(111). The CÀ S activation reaction is initiated at low annealing temperature and yields unsaturated hydrocarbon chains interconnected in a fully conjugated reticulated network. High-resolution atomic force microscopy imaging reveals the opening of the thiophenyl rings and the presence of trans-and cis-oligoacetylene chains as well as pentalene units. The chemical transformations we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 105 publications
(59 reference statements)
1
8
0
Order By: Relevance
“…Concerning the type-2 chains, they are partially cross-linked and are about 8–24 nm long and 1–3 nm wide, in line with typical sizes for covalent polymerization of similar systems based on small aromatic precursors. 36,41–44 The presence of 1D extended chains testifies that both active sites designed for covalent coupling are activated at this temperature, together with possible co-operating metal–organic bonds. Nevertheless, due to their intricate and stochastic structure, the chain analysis does not allow a clear assignment of precursor evolution upon coupling.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Concerning the type-2 chains, they are partially cross-linked and are about 8–24 nm long and 1–3 nm wide, in line with typical sizes for covalent polymerization of similar systems based on small aromatic precursors. 36,41–44 The presence of 1D extended chains testifies that both active sites designed for covalent coupling are activated at this temperature, together with possible co-operating metal–organic bonds. Nevertheless, due to their intricate and stochastic structure, the chain analysis does not allow a clear assignment of precursor evolution upon coupling.…”
Section: Resultsmentioning
confidence: 97%
“…The Cu(111) surface was chosen as the reaction template due to its hexagonal symmetry and high reactivity 36 with respect to other coinage metals, in particular towards halogenated precursors. 4,18,37 Also, the copper surface is expected to favor the flat adsorption of the precursor that has an intrinsically 3D structure.…”
Section: Introductionmentioning
confidence: 99%
“…The S 2p spectra (Figure 2b) of the NSC samples exhibited one distinct peak at 164.4 eV, corresponding to thiophene-derived C−S−C bonds. [48,49] The absence of a peak corresponding to S(0) suggests that the S species are incorporated into the carbon matrix. Particularly, the N−S peak, which indicates a covalent bond between the S and N atoms, was not detected because of the high energy barrier for bond formation.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of existing on-surface covalent polymerizations are based on coupling reactions, including the well-developed dehalogenation polymerization of halogenated hydrocarbons and the dehydrogenation polymerization of alkanes, , alkenes, alkynes, , and silanes . Moreover, other examples involving coupling reactions, such as decarboxylation polymerization of carboxylic acids and deoxidation polymerization of aldehydes, have been reported on surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…In the reported on-surface coupling reactions, the R–X functional group is activated and subsequently cleaved, forming a monoradical intermediate R· via the dissociation of X·. , In contrast, the ring-opening of a functional group could produce a diradical intermediate through the cleavage of the ring, which may bring new reaction modes that result in the formation of novel polymers. For example, the heterocyclic ring-opening reactions, such as on-surface desulfurization of thiophene, deconstruction of porphyrin and N -doped nanographene, and the ring-opening polymerization of melamine, have been reported to generate a variety of novel nanostructures. Recently, Gao et al reported a debromination ring-opening coordination reaction of hexabromobenzene to synthesize C6–Ag organometallic polyyne …”
Section: Introductionmentioning
confidence: 99%